Уравнения: 1,2(2х-4)+0,6=3х-3,6 4(3-7у)+10=-10у-86 5-3(2х-1)=4х-22 2(1,2у+5)-1=2у-6,6 17х+0,9=2х 9-2(х-4)2х-13 -4(2+3х)+11=-15х-3 0,2(3у+2)=2,6у-1,6

1

Ответы и объяснения

Лучший Ответ!
  • lili89
  • почетный грамотей
2012-05-23T00:16:30+04:00

1,2*(2х-4)+0,6 = 3х-3,6

2,4х-4,8 +0,6 = 3х-3,6

2,4х-3х = -3,6-0,6+4,8

-0,6х = 0,6

х = 0,6:(-0,6)

х = -1

1,2*(2*(-1)-4)+0,6 = 3*(-1)-3,6

1,2*(-6)+0,6 = -3-3,6

-7,2+0,6 = -6,6

Ответ: -1.

 

4(3-7у)+10=-10у-86

12-28у+10 = -10у-86

-28у+10у = -86-10-12

-18у = -108

у = -108:(-18)

у = 6

4*(3-7*6)+10 = -10*6-86

4*(-39)+10 = -60-86

-156+10 = -146

Ответ: 6. 

 

5-3(2х-1)=4х-22

5-6х+3 = 4х-22

-6х-4х = -22-3-5

-10х = -30

х = -30:(-10)

х = 3

5-3*(2*3-1) = 4*3-22

5-3*5 =12-22

5-15 = -10

Ответ: 3. 

 

2(1,2у+5)-1=2у-6,6

2,4у+10-1 = 2у-6,6

2,4у-2у = -6,6+1-10

0,4у = -15,6

у = -15,6:0,4

у = -39

2*(1,2*(-39)+5)-1 = 2* (-39)-6,6

2*(-41,8)-1 = -78-6,6

-83,6-1 = -84,6 

Ответ: -39. 

 

17х+0,9=2х  

17х-2х = -0,9

15х =-0,9

х = -0,9:15

х= -0,06

17*(-0,06)+0,9 = 2*(-0,06)

-1,02+0,9 = -0,12

Ответ: -0,06. 

 

9-2(х-4) = 2х-13

9-2х+8 = 2х-13

-2х-2х = -13-8-9

-4х = -30

х =-30: (-4)

х = 7,5

9-2*(7,5-4) = 2*7,5-13

9-7 = 15-13 = 2

Ответ: 7,5.

 

-4(2+3х)+11=-15х-3

-8-12х+11 = -15х-3

-12х+15х =-3-11+8

3х = -6

х= -6:3

х= -2

-4*(2+3*(-2))+11 = -15*(-2)-3

-4*(2+(-6))+11 = 30-3

16+11 = 27

Ответ: -2. 

 

0,2(3у+2)=2,6у-1,6

0,6у+0,4 = 2,6у-1,6

0,6у-2,6у = -1,6-0,4

-2у = -2

у = 1

0,2*(3*1+2) = 2,6*1-1,6

0,2*5 = 2,6-1,6=1

Ответ: 1.